Gum to keep desert in place - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The US Agency for International Development (USAID), the American Soft Drink Association and the Importer Services Corporation (ISC) have signed an agreement with various states in northern Nigeria to expand the production of Arabic gum (Acacia)....